Handling pointers and unstructured statements in the forward computed dynamic slice algorithm - Faragó, Csaba; Gergely, Tamás (Acta Cybernetica, 2002)
Different program slicing methods are used for debugging, testing, reverse engineering and maintenance. Slicing algorithms can be classified as a static slicing or dynamic slicing type. In applications such as debugging the computation of dynamic slices is more preferable since it can produce more precise results. In a recent paper [5] a new so-called "forward computed dynamic slice" algorithm was introduced. It has the great advantage compared to other dynamic slice algorithms that the memory requirements of this algorithm are proportional to the number of different memory locations used by the program, which in most cases is much smaller than the size of the execution history. The execution time of the algorithm is linear in the size of the execution history. In this paper we introduce the handling of pointers and the jump statements (goto, break, continue) in the C language.